Perfusion imaging findings, and outcomes between computed tomography perfusion selected basilar artery occlusion and anterior circulation stroke patients undergoing endovascular treatment - Xiaofeng Cai (PLoS ONE, 2026)
Background Basilar artery occlusion (BAO) is a severe form of ischemic stroke associated with high morbidity and mortality. Whether BAO patients derive similar benefits from CT perfusion (CTP)-guided endovascular treatment (EVT) as those with anterior circulation stroke (ACS) remains unclear. Aim This study aimed to compare the efficacy and safety of EVT based on computed tomography (CT) perfusion between patients with BAO and those with ACS. Methods This analysis was conducted using data from a prospective multicenter Registry on International Stroke Perfusion Imaging. A total of 256 patients with 36 BAO and 220 ACS who received CTP-guided EVT were included. Propensity score matching (PSM) in a 1:2 ratio was performed to adjust for baseline imbalances. Multivariate logistic regression was used to identify independent predictors of mRS 3–6 at 90 days as poor functional outcome and mortality. Results Prior to matching, BAO patients had higher baseline NIHSS scores (24.0 ± 9.8 vs. 15.2 ± 6.4, p < 0.001), smaller ischemic core volumes (8.7 ± 11.4 mL vs. 33.2 ± 38.9 mL, p < 0.001), and higher mismatch ratios (0.9 ± 0.1 vs. 0.7 ± 0.2, p < 0.001) than ACS patients. After matching, BAO patients had significantly shorter door-to-reperfusion time (3.2 ± 1.1 vs. 4.3 ± 2.9 hours, p = 0.007) and lower rates of hemorrhagic transformation (19.4% vs. 48.6%, p = 0.006). Multivariate analysis identified baseline NIHSS score (OR = 1.052, 95% CI: 1.013–1.092, p = 0.009) and ASPECT score (OR = 0.813, 95% CI: 0.682–0.969, p = 0.021) as independent predictors of poor outcome, while age (OR = 1.037, 95%CI: 1.006–1.069, p = 0.020) and baseline NIHSS score (OR = 1.070, 95% CI: 1.024–1.119, p = 0.002) were independent predictors of mortality. No significant differences were observed in 90-day functional independence (mRS 0–2) or mortality between BAO group and ACS group. Conclusions Despite presenting with more severe neurological deficits, BAO patients treated with CTP-guided EVT achieved comparable functional outcomes and mortality to ACS patients, with shorter reperfusion times and fewer hemorrhagic complications. CTP-based selection may facilitate effective EVT in BAO.